Pemanfaatan Media Film sebagai Sumber Pembelajaran Sejarah dalam Upaya Meningkatkan Minat Belajar Siswa di Kelas IX IPS Madrasah Aliyah Tahfizil Quran - Ayu, Dedek; Nababan, Surya Aymanda; Hardiyansyah, Muhammad Ricky; Kusbiantoro, Dedi; Azis, Abdul; Darma, Aditya (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2023)
In general, history teachers tend to use methods such as lectures and discussions, using simple media such as blackboards and printed materials like books. However, teachers in Madrasah Tahfizil Qur'an use films as a teaching media, which motivates students to learn and facilitates their understanding and mastery of the subject. This study aims to describe the technique of utilizing films by teachers as a learning media in history, the suitability between the film media and the subject matter, and the students' response to the use of films as a source of learning in history. The research method used is qualitative descriptive method. Data collection techniques and tools include observation, interviews, and documentation. Data processing is conducted using qualitative descriptive analysis techniques. Then, the data is compared, checked for validity, and described. The findings of the field research are as follows: (1) The utilization of film media as a source of learning in history in Madrasah Tahfizil Qur'an is good. History teachers have mastered the steps of using film media and have employed appropriate strategies in teaching. (2) Film media in history learning in Grade XI of Madrasah Tahfizil Qur'an can only be used for specific learning objectives and competencies. (3) The students' response to the utilization of films as a learning media in history in Grade XI of Madrasah Tahfizil Qur'an is very positive. The use of film media in history learning leaves a positive impression on the students, and they are motivated to learn because they can effectively grasp the conveyed material.